The validity and reliability of the My Jump 2 app for measuring vertical stiffness in male college players - Wang, Yizhang; Wang, Xintang; Luan, Chenglin; Shan, Wei; Gong, Lijing (Frontiers in Sports and Active Living, 2024)
Background: Vertical stiffness (Kvert) can be used to evaluate sports performance and injury risk in players. The My Jump 2 smartphone application (App), is increasingly being used by researchers, coaches, and players in the competitive sports field. We aimed to analyze the reliability and concurrent validity of the My Jump 2 app for measuring Kvert in male college players.Methods: Twenty male college players (10 soccer players, 10 basketball players; age, 20.2±1.3 years old; weight, 76.4±6.0kg; height, 178.3±4.7cm) volunteered to take part in this study. Three drop jumps were performed by participants from 30cm to 40cm on a force platform and retested after three days. All the jumps were recorded by both the Force platform and the My Jump 2 app.Data obtained from the above two devices were compared using the paired t tests, intraclass correlation coefficient (ICC), coefficient of variation (CV), Pearson product moment correlation coefficient (r), Bland-Altman plots, and one-way regression.Results: There was almost perfect agreement between measurement instruments for the Kvert value (ICC>0.972, 95%CI=0.954-0.992, P<0.01). Almost perfect agreement was observed between evaluators (ICC>0.989, 95%CI=0.981-0.997, P<0.05). Also, the My Jump 2 app showed excellent intra-rater reliability in all participants (ICC = 1.000, 95% CI = 1.000-1.000, P<0.001).The My Jump 2 showed good variability when measuring Kvert at T1 30cm (CV = 5.4%), T1 40cm (CV = 6.7%), T2 30cm (CV = 5.0%), and T2 40cm (CV = 10.3%). The test-retest reliability of My Jump 2 was moderate to good at 30 cm (ICC = 0.708, 95% CI = 0.509-0.827); however, it was lower to moderate at 40cm (ICC = 0.445）. Very large correlations were observed between the force platform and the My Jump 2 for Kvert (r > 0.9655, P < 0.001).The My Jump 2 smartphone application showed excellent reliability and intra-rater consistency in measuring Kvert in male college players. While demonstrating excellent intra-rater consistency and strong agreement with force platform measurements, it showed slightly lower reliability at higher jump heights. Overall, the My Jump 2 app is a valid tool for evaluating Kvert in college players with careful consideration of its limitations, particularly at higher jump heights.